On the Optimality of Finite Constellations from Algebraic Lattices - Interlando, J. Carmelo [UNESP]; Elia, Michele; Pires da Nóbrega Neto, Trajano [UNESP] (Elsevier, 2001)
A construction technique of finite point constellations in n-dimensional spaces from ideals in rings of algebraic integers is described. An algorithm is presented to find constellations with minimum average energy from a given lattice. For comparison, a numerical table of lattice constellations and group codes is computed for spaces of dimension two, three, and four. © 2001.
Keywords: Algebraic lattice; Linear labeling; Signal constellation